1996
DOI: 10.1089/aid.1996.12.1687
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Heterogeneity of HIV Type 1 in Russia: Identification of H Variants and Relationship with Epidemiological Data

Abstract: HIV-genetic subtypes were analyzed in 130 subjects from the Russian Federation, by the HMA technique. Six subtypes were identified in heterosexuals, including A, B, C, D, G, and H; however, homosexual men were infected predominantly with the B subtype (33 of 35). The subtype A isolates were found in population of intravenous drug users. HMA successfully identifies 128/130 DNA samples; the phylogenetic analysis of the V1/V5 gp120 encoding region derived from another two samples demonstrated that these isolate b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 7 publications
0
9
0
2
Order By: Relevance
“…All primers have been described. 6,15 Primers ED12, ES7, and ES8 have been used for the successful amplification of HIV-1 strain from all group M subtypes [16][17][18][19] and primer KK1 was designed with the consensus sequence of the HIV-1 M group. After nested PCR (nPCR), the cDNA from four patients yielded positive signals by agarose gel electrophoresis and ethidium bromide staining.…”
Section: Rt-pcr Amplification Of Hiv-1 From 1978-1979 Seramentioning
confidence: 99%
“…All primers have been described. 6,15 Primers ED12, ES7, and ES8 have been used for the successful amplification of HIV-1 strain from all group M subtypes [16][17][18][19] and primer KK1 was designed with the consensus sequence of the HIV-1 M group. After nested PCR (nPCR), the cDNA from four patients yielded positive signals by agarose gel electrophoresis and ethidium bromide staining.…”
Section: Rt-pcr Amplification Of Hiv-1 From 1978-1979 Seramentioning
confidence: 99%
“…Up to December 1995, there were only 1072 HIV-1 cases officially registered in Russia, and 72.0% of the cases with known risk factors were infected through sexual contacts. HIV-1 belonging to seven different genetic subtypes (A-D, F-H) [Bobkov et al, 1996;Leinikki et al, 1996] as well as three recombinant variants (CRF01_AE [Bobkov et al, 1997a], CRF02_AG ] and the gagDenvG [Bobkov et al, 1998a] recombinant) was found. Since that time, HIV-1 has been introduced into the injecting drug user (IDU) population, and the HIV-1 epidemic in Russia entered its second phase.…”
Section: Introductionmentioning
confidence: 99%
“…4 In Europe, HIV-1 infection is currently dominated by subtype B but a growing mixture of HIV-1 subtypes has been reported. Studies in France, 5,6 Sweden, 7 Denmark, 8 Switzerland, 9 the United Kingdom, 10 Spain, 11,12 Greece, 13 Cyprus, 14 Belgium, 15,16 The Netherlands, 16 Germany, 17 Italy, 18 Austria, 19 Norway, 20 and Eastern Europe [21][22][23][24][25][26][27] have detected most of the group M clades. Group O has been reported in France, 6 Germany, 28 Belgium, 29 and Spain.…”
Section: Introduction Tmentioning
confidence: 99%